Forecasting the Remaining Duration of an Ongoing Solar Flare - Jeffrey W. Reep; Will T. Barnes (Space Weather)
Abstract The solar X‐ray irradiance is significantly heightened during the course of a solar flare, which can cause radio blackouts due to ionization of the atoms in the ionosphere. As the duration of a solar flare is not related to the size of that flare, it is not directly clear how long those blackouts can persist. Using a random forest regression model trained on data taken from X‐ray light curves, we have developed a direct forecasting method that predicts how long the event will remain above background levels. We test this on a large collection of flares observed with GOES‐15, and show that it generally outperforms simple linear regression, giving a median error of less than 2 min for the approximate end time of a flare. This random forest model is computationally light enough to be performed in real time, allowing for the prediction to be made during the course of a flare.